The Role of Equality and Non-Discrimination in Shaping Constitutional Gender Dynamics and Safeguarding Family Life - Danėlienė Ingrida (Baltic Journal of Law & Politics, 2025)
The article studies the constitutional context and preconditions for shaping the constitutional gender dynamics in the Republic of Lithuania, establishing the constitutional threshold for better protection of the right to family life, equality between men and women and other gender rights. It identifies the constitutional principles of equality and non-discrimination that (along with the influence of supranational law) have had the most influence in the slow, but generally coherent development of the said constitutional concepts.